A Study on Impact of Green Human Resource Management Practice on Organizations Performance Affecting Increased Sales and Profits in IT Sector in Bangalore (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the term of implementing the performance of an organization, Human Resource Management leads a heavy part in this field for making the crucial strategies and decisions. This provides the organization to maintain and develop its sustainability culture. The main motive of Green Human Resource Management is to stimulate sustainable development through Human Resource Management. In the terms of development, the activities of Green HRM (Green Human Resource Management) are spreading realization among the workers and the employees by adopting new strategies in the work field such as saving energy at workplace, implementation of E-HRM, work from home and mostly taking precautions to protect the mother environment. From the past few years, the rate of global concerns has increased in the matter of environmental matters..